2006
DOI: 10.1107/s1600536806031254
|View full text |Cite
|
Sign up to set email alerts
|

Hydrogen-bonding patterns in 2-amino-4,6-dimethylpyrimidinium picrate

Abstract: Key indicatorsSingle-crystal X-ray study T = 153 K Mean (C-C) = 0.004 Å Disorder in main residue R factor = 0.060 wR factor = 0.201 Data-to-parameter ratio = 11.5For details of how these key indicators were automatically derived from the article, see

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
10
0

Year Published

2007
2007
2011
2011

Publication Types

Select...
6

Relationship

4
2

Authors

Journals

citations
Cited by 8 publications
(13 citation statements)
references
References 6 publications
3
10
0
Order By: Relevance
“…However, in cation B and compound (II), the protonated N atoms (N1B and N1) do not form bifurcated hydrogen bonds with the nitro group (O4B and O7) of the picrate anion, resulting in only two rings with graph-set notations R 1 2 (6) and R 2 1 (6) ( Table 4). This type of interaction has also been reported in the crystal structure of 2-amino-4,6dimethylpyrimidinium picrate (Subashini et al, 2006). Ions A and B form individual chains via C-HÁ Á ÁO hydrogen bonds.…”
Section: Figuresupporting
confidence: 72%
“…However, in cation B and compound (II), the protonated N atoms (N1B and N1) do not form bifurcated hydrogen bonds with the nitro group (O4B and O7) of the picrate anion, resulting in only two rings with graph-set notations R 1 2 (6) and R 2 1 (6) ( Table 4). This type of interaction has also been reported in the crystal structure of 2-amino-4,6dimethylpyrimidinium picrate (Subashini et al, 2006). Ions A and B form individual chains via C-HÁ Á ÁO hydrogen bonds.…”
Section: Figuresupporting
confidence: 72%
“…For related structures, see: Muthamizhchelvan et al (2005a,b,c); Subashini et al (2006); Narayana et al (2008). For standard bond lengths, see: Allen et al (1987).…”
Section: Related Literaturementioning
confidence: 99%
“…The crystal structures of compounds similar to ethylenediammonium picrate, 3-(dimethylammonio)propanaminium dipicrate and triethylaminium picrate (Muthamizhchelvan et al, 2005a(Muthamizhchelvan et al, , 2005b(Muthamizhchelvan et al, , 2005c, 2-amino-4,6-dimethylpyrimidinium picrate (Subashini et al, 2006) and 2-aminopyrimidinium picrate (Narayana et al, 2008) have been reported. In continuation of our work on picrates of biologically important molecules (Harrison et al, 2007;Swamy et al, 2007), we have prepared a new picrate of ethylenediammonium hydrate, [C 7 H 8 N 4 O 8 ] and its crystal structure is reported.…”
Section: S1 Commentmentioning
confidence: 99%
“…For related structures, see: Ferguson et al (1984); Glidewell et al (2003); Narayana et al (2008); Scheinbeim & Schempp, (1976); Schlueter et al (2006); Subashini et al (2006). For density functional theory, see: Hehre et al (1986); Schmidt & Polik (2007).…”
Section: Related Literaturementioning
confidence: 99%